Structural behaviour of concrete filled stiffened steel tubes column / Clotilda Petrus - Petrus, Clotilda (2011)
A concrete filled steel tubes (CFST) column is constructed by filling a hollow structural steel tube with concrete. As one of structural element, CFST column has high load bearing capacity, excellent earthquake-resistance, good ductility, high fire resistance and its higher stiffness delay the onset of local buckling. Besides that, the steel tube can function as a permanent form work as well as reinforcement, thus more economical. The promising features of CFST steel column as an excellent earthquake resistance might be of interest for structural engineers or designers in finding solution to the increasing threat of near and far-field earthquakes in our country. Composite columns of this type have a very good potential to be used in structural applications.